(untitled) (FUDMA JOURNAL OF SCIENCES, 2021)
The study aims to evaluate the effects of feeding different protein levels on the resumption of postpartum ovarian activity by measuring serum estradiol (E2) and progesterone (P4) concentrations bi-weekly starting one week postpartum in three genotypes of sheep (Yankasa, Uda and Balami). Eighteen (18) multiparous sheep with aged range of 2.5 – 3 years old consisting of six (6) each of Yankasa, Uda and Balami breeds were divided into three groups and reared on different protein concentrations. The protein concentrations were 15.2% (high), 9.5% (medium) and 6.5% (low). Results showed a gradual increase of estradiol in both Yankasa and Uda breeds fed low protein diet from 100 – 3000 concentration. However, Uda breed had the highest value of estradiol when both medium and high protein diets were fed to the three genotypes of sheep. Nevertheless, Yankasa sheep had more consistent values of progesterone when fed low protein diet compared to Balami and Uda. Also Uda breed recorded the highest progesterone values in both medium and high protein diets among the three genotypes followed by Yankasa sheep. All the three genotypes returned to estrous earlier on high protein concentration followed by those on medium protein level. It is concluded that increase protein concentration hastened resumption of ovarian cyclicity and thereby leading to increase fertility in sheep